Weld integrity assurance: a case study for prioritising welding quality deterioration factors in piping components fabrication. Issue 2 (1st January 2012) - Ratnayake, R.M. Chandima; Vik, K.T.
Failures related to major structures in the long-term have highlighted the devastating consequences when poor welding practices and procedures compromise the integrity of the welds that hold them together. The inspection and testing alone do not prevent defects in welding, as it is acknowledged that defects occur in welds because of inappropriate welding procedures and welder performance. An important part of any quality control programme is assuring that the personnel have the appropriate skill to perform the work. This is mainly due to the fact that the execution of critical welds requires skilled welders who will follow the project welding requirements imposed by the regulations. In this manuscript, a methodology is proposed to prioritise the quality deterioration factors that are attributed to welding personnel performance. A case study is performed to verify the applicability of the methodology.